2019
DOI: 10.1161/circulationaha.118.036701
|View full text |Cite
|
Sign up to set email alerts
|

Components and Trends in Door to Treatment Times for Endovascular Therapy in Get With The Guidelines-Stroke Hospitals

Abstract: Background: Endovascular therapy (EVT) is standard of care in patients with acute disabling ischemic stroke attributable to large-vessel occlusion and is more effective when delivered quickly. It is currently unclear whether time targets achieved in clinical trials can be achieved in clinical practice. We describe interval times from patient arrival in the emergency department (door) to first pass (treatment initiation) in patients receiving EVT within Get With The Guidelines-Stroke hospitals and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
0
36
0
2
Order By: Relevance
“…17 Three American Registry Studies (2014–2016) reported a DTGT of 80–123 min. 14,18,19 In a registry study, recruiting patients in southern Germany, DTGT was 90 min in CSC patients and 64 min in PSC patients. 20 However, although comprehensive stroke centers in the GSR–ET achieve adequate treatment times by national and international comparison, most contributing centers are high-volume centers, and for these, a current international consensus statement suggests a DTGT within 62 min.…”
Section: Discussionmentioning
confidence: 99%
“…17 Three American Registry Studies (2014–2016) reported a DTGT of 80–123 min. 14,18,19 In a registry study, recruiting patients in southern Germany, DTGT was 90 min in CSC patients and 64 min in PSC patients. 20 However, although comprehensive stroke centers in the GSR–ET achieve adequate treatment times by national and international comparison, most contributing centers are high-volume centers, and for these, a current international consensus statement suggests a DTGT within 62 min.…”
Section: Discussionmentioning
confidence: 99%
“…Because the effect of endovascular treatment (EVT) for ischaemic stroke is strongly time-dependent, it is important to optimise prehospital and in-hospital workflows to reduce unnecessary treatment delays. 1 3 Interhospital transfers are an important cause of treatment delay and are associated with worse functional outcome. 4 , 5 Prehospital stroke scales may be helpful for the selection of patients with a high likelihood of a large vessel occlusion (LVO), to bypass the primary stroke centre for direct transport to an intervention centre capable of EVT and thereby avoiding time-consuming interhospital transfers.…”
Section: Introductionmentioning
confidence: 99%
“… Imaging assessment committee: Charles BLM Majoie3(chair); Wim H van Zwam6; Aad van der Lugt2; Geert J Lycklama à Nijeholt13; Marianne AA van Walderveen10; Marieke ES Sprengers3; Sjoerd FM Jenniskens27; René van den Berg3; Albert J Yoo 38 ; Ludo FM Beenen3; Alida A Postma6; Stefan D Roosendaal3; Bas FW van der Kallen13; Ido R van den Wijngaard13; Adriaan CGM van Es2; Bart J Emmer , 3; Jasper M Martens12; Lonneke SF Yo33; Jan Albert Vos8; Joost Bot 36 ; Pieter-Jan van Doormaal2; Anton Meijer27; Elyas Ghariq13; Reinoud PH Bokkers29; Marc P van Proosdij 37 ; G Menno Krietemeijer33; Jo P Peluso26; Hieronymus D Boogaarts20; Rob Lo18; Dick Gerrits 35 ; Wouter Dinkelaar 2 Auke PA Appelman29; Bas Hammer16; Sjoert Pegge27; Anouk van der Hoorn29; Saman Vinke20. …”
unclassified
“…Anpassung der lokalen Schlaganfallversorgungskonzepte [96]. In einer Metaanalyse konnte gezeigt werden, dass schnelle Prozesszeiten für die Thrombolyse einhergehen mit ebenfalls schnellen Zeiten für die endovaskuläre Therapie [97]. Die Pilotstudie zum "One-Stop-Management" (wenn NIHSS > 9 Punkte: Rettungsdienst-Übergabe des Patienten direkt im Angiografieraum und Flachdetektor-Computertomografie) konnte eine signifikante Reduktion der Zeit von Eintreffen des Patienten bis zur Leistenpunktion belegen (54,5 min versus 20,5 min, p 0,001) [98].…”
Section: Mechanische Thrombektomie Als Interdisziplinäre Herausforderungunclassified